2023
DOI: 10.3389/fcell.2023.1142629
|View full text |Cite
|
Sign up to set email alerts
|

Granulosa cell-derived extracellular vesicles mitigate the detrimental impact of thermal stress on bovine oocytes and embryos

Abstract: Climate change-induced global warming results in rises in body temperatures above normal physiological levels (hyperthermia) with negative impacts on reproductive function in dairy and beef animals. Extracellular vesicles (EVs), commonly described as nano-sized, lipid-enclosed complexes, harnessed with a plethora of bioactive cargoes (RNAs, proteins, and lipids), are crucial to regulating processes like folliculogenesis and the initiation of different signaling pathways. The beneficial role of follicular fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Additionally, Khan et al [ 47 ] reported that HS significantly compromises granulosa cells, leading to suboptimal oocyte development. This is further supported by studies that found HS compromises the mRNA expression levels of Moloney sarcoma oncogene (MOS), growth factor 9 (GDF9), and POU domain, class 5, transcription factor 1 (POUF51), which are crucial for oocyte development and competence, ultimately resulting in poor-quality oocytes and impaired embryonic development [ 60 , 61 , 70 , 71 , 72 ]. Figure 1 demonstrates the adverse impact of heat stress on phenotypic traits related to mammalian reproductive traits.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, Khan et al [ 47 ] reported that HS significantly compromises granulosa cells, leading to suboptimal oocyte development. This is further supported by studies that found HS compromises the mRNA expression levels of Moloney sarcoma oncogene (MOS), growth factor 9 (GDF9), and POU domain, class 5, transcription factor 1 (POUF51), which are crucial for oocyte development and competence, ultimately resulting in poor-quality oocytes and impaired embryonic development [ 60 , 61 , 70 , 71 , 72 ]. Figure 1 demonstrates the adverse impact of heat stress on phenotypic traits related to mammalian reproductive traits.…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, HS exerts detrimental effects on follicle quality and hormonal equilibrium, contributing to a decline in estrus [ 54 , 55 , 56 , 57 , 58 ]. Specifically, granulosa cells responsible for estradiol production are adversely affected by HS, resulting in decreased estradiol production and subsequent disruption of the estrous cycle in cattle [ 59 , 60 , 61 ]. HS has also been shown to influence corticoid levels, luteinizing hormone (LH), and plasma progesterone in cattle, with alterations in hypothalamus and pituitary gland function leading to changes in the secretion of reproductive hormones [ 9 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-documented that the expression level of particular miRNAs are key during development [29,30] and stress responses [31,32], and that EVs play an important role in transferring miRNA cargoes between cells [33]. Alterations in the release and uptake of EVs are associated with pathologies including cancer [34] and cellular stress [32,[35][36][37][38][39].…”
Section: Unpacking Ev Cargomentioning
confidence: 99%